An association between maternal diet and colonic diverticulosis in an animal model. Issue 3 (September 1996) - Wess, L; Eastwood, M; Busuttil, A; Edwards, C; Miller, A
Abstract : BACKGROUND/AIMS: Maternal diet may have an effect on the health of the offspring in middle and later life. This study used the laboratory rat as an animal model to examine whether the fibre content of the maternal diet during pregnancy affected subsequent development of colonic diverticula in the offspring fed lifelong fibre deficient or higher fibre diets. METHODS: The parents of experimental animals were fed either a diet that was known to predispose to colonic diverticulosis or a control diet for one month prior to mating. The offspring were fed one of these diets for 18 months. The incidence of colonic diverticulosis, submucosal collagen content, collagen solubility in weak acid, and the composition of intestinal contents were then measured. RESULTS: Offspring of rats fed a higher fibre diet from higher fibre diet fed parents had 0% incidence of colonic diverticulosis. When offspring (regardless of parental diet) were fed a low fibre diet for life the acid solubility was lowered compared with rats fed lifelong higher fibre diet mean (SD) (0.044 (0.0007) v 0.073 (0.0015) sigmoid colon (ratio of soluble:insoluble collagen)); 21.1% had diverticulosis and there was reduced fibre fermentation. However, when the diet of the parents of the fibre deficient diet fed rats was considered, the animals whose mothers had a fibre deficient diet had lower acid solubility (0.032 (0.0007)) and an increased incidence of colonic diverticulosis (42.1%) than the animals fed a fibre deficient diet from higher fibre diet fed parents (p < 0.01 in all instances). CONCLUSION: Maternal diet and the subsequent nutrition of the progeny seem to be of importance in the development of colonic diverticulosis in the rat.